Growth Performance of Timber Species under Forest Plantations in Different Agro-Climatic Zone of Jharkhand, India - Singh, Madan Prasad; Singh, Sanjay (Indian Forester, 2015)
Forest department in Jharkhand undertook large scale plantations in the forestland. Trees planted on forest lands for primarily environmental benefits are being managed as per the needs of local people who have rights in those forests. These plantations have enhanced the forest cover by 942 Km2 between 2001 and 2011. These plantations created all over the state provided an excellent opportunity to evaluate the growth performance of timber species in field conditions. This paper presents the growth performance of timber species under plantation forestry in different agroclimatic conditions (subzones or regions) in the state of Jharkhand. The scientific understanding of growth performance of these species would help the entrepreneurs and forest department in exploring the different combination of species for economic viability as well as ecological benefits. There is nearly 2.5 million ha fallow agricultural land area available for tree planting under private forestry in Jharkhand. However, among other support systems for tree cultivation on such lands, the choice of species and management practices are important component for tree growers.